A PLA composite based on MBS melt blending modification and a preparation method thereof
Patent Information
- Application Number
- CN202611325925.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-29
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了一种基于MBS熔融共混改性的PLA复合材料及其制备方法,解决了常规聚乳酸三元共混体系在引入低分子树脂改善熔体流动性时,因均相剪切失控击穿共聚物核壳弹性骨架,导致增韧机制失效与流变学劣化相绑定的零和博弈的问题
[0028]1、本发明通过在双螺杆挤出流场中构筑由反向螺纹元件与左旋捏合块组合的动态熔体密封段,阻断了低粘度流体的逆向回流路径,将聚乳酸与甲基丙烯酸甲酯-丁二烯-苯乙烯共聚物的强剪切相容过程独立封装,剥夺了后续添加剂破坏共聚物丁二烯橡胶核的剪切动力,在完整定格核壳增韧相结构的基础上,避免了复合材料出现脆化,增强了体系抵抗外部冲击的韧性。
Smart Images

Figure CN122878729A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of PLA composite material technology, specifically to a PLA composite material based on MBS melt blending modification and its preparation method. Background Technology
[0002] Polylactic acid (PLA) has shown great potential as an environmentally friendly polymer material in the field of fused deposition modeling (FDM) 3D printing. However, the inherent brittleness and extremely low elongation at break caused by the highly regular macromolecular chain segments restrict the molding quality of complex stress-bearing structural parts. The industry usually introduces methyl methacrylate butadiene styrene copolymer with a core-shell structure as an elastomer dispersion phase to absorb the impact energy of matrix fracture. However, doping such elastomer island phases into the PLA matrix will induce a sharp increase in the frictional resistance between polymer chain segments, resulting in an increase in the apparent viscosity and a decrease in the flow rate of the composite melt, which will cause poor filament output or even dead zone blockage during extrusion printing.
[0003] To overcome the rheological barriers caused by high viscosity and simultaneously improve interlayer adhesion in printing, conventional techniques involve blending low molecular weight petroleum resin into the blend system as a thickener and lubricant. However, existing extrusion processing systems generally adopt the traditional blending mode of direct dry mixing and feeding at the main feed port. Under the processing environment of strong shear force field and continuous high temperature in the entire range of twin screws, low viscosity liquid petroleum resin not only cannot be uniformly free in the free volume of polylactic acid continuous phase, but also breaks through the outer shell of the copolymer toughening phase, invades the butadiene rubber core, and causes elastomer swelling and even micro-skeletal collapse.
[0004] The disordered destruction of this microscopic phase structure severs the transmission link of the elastomer to absorb external impact energy, causing the composite material to drastically reduce its toughness while achieving an improvement in apparent fluidity. Existing technologies have always been constrained by the single flow field configuration and the spatiotemporal overlap of component phase transitions, making it impossible to build an isolation between strong shear dispersion and weak shear coating. This results in the two core modification mechanisms of plasticizing lubrication and rubber phase toughening falling into a mutually exclusive zero-sum game. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a PLA composite material based on MBS melt blending modification and its preparation method. This solves the zero-sum game problem in conventional polylactic acid ternary blend systems where the introduction of low molecular weight resins to improve melt flow results in the failure of the toughening mechanism and the degradation of rheology due to the uncontrolled breakdown of the copolymer core-shell elastic skeleton caused by homogeneous shear.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a PLA composite material based on MBS melt blending modification, wherein the composite material comprises the following components by weight percentage:
[0007] Polylactic acid: 83.0%-88.5%;
[0008] Methyl methacrylate-butadiene-styrene copolymer: 10.0%-15.0%;
[0009] C5 petroleum resin: 1.5%-2.0%;
[0010] The sum of the weight percentages of the above components is 100%.
[0011] Preferably, the methyl methacrylate-butadiene-styrene copolymer is a copolymer with a core-shell structure, wherein the inner core of the core-shell structure is a butadiene rubber phase, and the outer shell is composed of styrene and methyl methacrylate.
[0012] Preferably, in the microstructure of the composite material, the methyl methacrylate-butadiene-styrene copolymer is dispersed as an island phase in the continuous phase composed of polylactic acid, and the C5 petroleum resin is distributed between the molecular chains of the continuous phase.
[0013] A method for preparing PLA composite materials based on MBS melt blending modification is employed using a twin-screw extruder. The twin-screw extruder is sequentially configured along the material conveying direction with a main plasticizing blending zone, a dynamic melt sealing section, a side-injection mixing zone, and an extrusion shaping zone. The preparation method includes the following steps:
[0014] S1. The dried polylactic acid and methyl methacrylate-butadiene-styrene copolymer are added to the main plasticizing blending zone through the main feed port for melt blending;
[0015] S2. The blended melt formed in step S1 enters the dynamic melt sealing section. The material is forcibly compressed and fills the cross-section of the barrel in the dynamic melt sealing section, forming a melt sealing zone that prevents gas-liquid backflow.
[0016] S3. The pre-molten C5 petroleum resin is injected through an interface located on the side wall of the barrel in the lateral injection mixing zone. The liquid C5 petroleum resin is then weakly sheared mixed with the blended melt that passes through the dynamic melt sealing section.
[0017] S4. The material mixed in step S3 enters the extrusion and shaping area for shaping, and is extruded through the die, cooled and pelletized to obtain the PLA composite material.
[0018] Preferably, in the twin-screw extruder, the dynamic melt sealing section is composed of a reverse threaded element and a left-handed kneading block, and the ratio of the section length of the dynamic melt sealing section to the diameter of the twin screw, L / D, is 2.0-3.0.
[0019] Preferably, in step S3, the liquid C5 petroleum resin is injected into the lateral injection mixing zone through a melt gear pump. The injection pressure of the melt gear pump is higher than the working melt pressure of the barrel in the lateral injection mixing zone, and the pressure difference is controlled between 0.5 MPa and 1.2 MPa.
[0020] Preferably, in step S1, the barrel heating temperature of the main plasticizing blending zone is set to 180℃-190℃;
[0021] In step S3, the barrel heating temperature of the lateral injection mixing zone is set to 160℃-165℃.
[0022] Preferably, in step S4, the temperature of the extrusion setting zone is set to 150℃-155℃; and the screw speed of the twin-screw extruder is set to 120rpm-180rpm.
[0023] Preferably, in step S3, the screw configuration set in the lateral injection mixing zone is a combination structure of a large lead forward wide pitch conveying element and a narrow toothed mixing element.
[0024] Preferably, before mixing in step S1, the polylactic acid and methyl methacrylate-butadiene-styrene copolymer are dried at 60℃-65℃ for 3.0h-4.0h.
[0025] In step S3, the C5 petroleum resin is preheated to 145°C-155°C until completely melted before injection;
[0026] In step S4, the extruded material is introduced into a water tank at 20℃-25℃ for traction cooling for 1.5m-2.0m, and the length of the cut particles is 2.5mm-3.0mm.
[0027] This invention provides a PLA composite material based on MBS melt blending modification and its preparation method. It has the following beneficial effects:
[0028] 1. This invention constructs a dynamic melt sealing section in the twin-screw extrusion flow field, which is composed of a reverse thread element and a left-handed kneading block. This blocks the reverse flow path of the low-viscosity fluid and independently encapsulates the strong shear compatibility process of polylactic acid and methyl methacrylate-butadiene-styrene copolymer. This deprives the subsequent additives of the shear force that would damage the butadiene rubber core of the copolymer. Based on the complete core-shell toughening phase structure, this invention avoids the embrittlement of the composite material and enhances the toughness of the system against external impacts.
[0029] 2. This invention introduces a micro-positive pressure differential lateral injection technology to cut pre-molten C5 petroleum resin into the cooled weak shear zone, confining the low molecular weight resin to only the free volume of the macromolecular chain segments of the polylactic acid continuous phase. At this time, the empty phase sequence isolation mechanism allows the low molecular weight resin to exert a precise molecular-level inter-chain lubrication effect, offsetting the increased matrix viscosity caused by the introduction of copolymer island phase nodes. It clears the rheological obstacles at the microscopic molecular slip level and solves the nozzle clogging defect caused by the slow melt flow of the filament during fused deposition modeling 3D printing.
[0030] 3. By anchoring the extreme values of additives in the ternary blend system, this invention transforms the initial tack of trace amounts of C5 petroleum resin into the driving force for molecular chain entanglement between printed layers while maintaining the rigidity of the polylactic acid matrix skeleton and the stability of the continuous phase network. This intervenes in the phase interface wetting process during molten deposition stacking, strengthens the interlayer adhesion of 3D printed parts in the Z-axis direction, and overcomes the problem of easy cracking of traditional molded parts while resolving the contradiction between material thickening and flow and maintaining deformation resistance and toughness. Attached Figure Description
[0031] Figure 1 This is a flowchart illustrating the overall process of the preparation method of the present invention.
[0032] Figure 2 This is one of the schematic diagrams of the preparation method of the present invention;
[0033] Figure 3 This is a second schematic diagram of the preparation method of the present invention;
[0034] Figure 4 This is the third schematic diagram of the preparation method of the present invention. Detailed Implementation
[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0036] See attached document Figure 1 -Appendix Figure 4 This invention provides a PLA composite material based on MBS melt blending modification, which, by weight percentage, consists of the following components:
[0037] Polylactic acid: 83.0%-88.5%;
[0038] Methyl methacrylate-butadiene-styrene copolymer: 10.0%-15.0%;
[0039] C5 petroleum resin: 1.5%-2.0%;
[0040] The sum of the weight percentages of the above components is 100%;
[0041] The methyl methacrylate-butadiene-styrene copolymer is a core-shell copolymer. The inner core of the core-shell structure is a butadiene rubber phase, and the outer shell is composed of styrene and methyl methacrylate. In the microstructure of the composite material, the methyl methacrylate-butadiene-styrene copolymer is dispersed as an island phase in the continuous phase composed of polylactic acid, and C5 petroleum resin is distributed between the molecular chains of the continuous phase.
[0042] Specifically, in the composite material, polylactic acid (PLA) serves as the matrix material, forming the continuous phase framework. The methyl methacrylate-butadiene-styrene copolymer, through its outer shell containing styrene and methyl methacrylate, undergoes molecular chain-level entanglement with the PLA matrix, thus fixing itself within the PLA continuous phase to form isolated island phase nodes. In the aforementioned component ratio, the PLA matrix weight percentage is defined as 83.0%-88.5%, providing fundamental mechanical support for the composite material; the methyl methacrylate-butadiene-styrene copolymer weight percentage is controlled within the range of 10.0%-15.0%, ensuring the stability of the PLA matrix. A uniformly dense island-phase dispersion network can be established in the continuous acid phase. As a low molecular weight nonpolar substance, C5 petroleum resin, limited by a trace ratio of 1.5%-2.0%, has its internal space located within the free volume between polylactic acid macromolecular segments. Combined with the barrier properties of the dense outer shell of methyl methacrylate-butadiene-styrene copolymer, the trace amount of C5 petroleum resin only coats the periphery of the island phase structure or remains free between polylactic acid segments, without penetrating the outer shell into the butadiene rubber phase. This avoids the swelling of the butadiene rubber core due to the absorption of low molecular weight resin, thus maintaining the integrity of the core-shell structure.
[0043] A method for preparing PLA composite materials based on MBS melt blending modification is described, using a twin-screw extruder. The twin-screw extruder is sequentially configured along the material conveying direction, comprising a main plasticizing blending zone, a dynamic melt sealing section, a side-injection mixing zone, and an extrusion shaping zone. Within the twin-screw extruder, the dynamic melt sealing section is composed of a combination of a reverse-threaded element and a left-handed kneading block, and the ratio of the section length of the dynamic melt sealing section to the twin-screw diameter (L / D) is 2.0-3.0. The preparation method includes the following steps:
[0044] S1. The dried polylactic acid and methyl methacrylate-butadiene-styrene copolymer are added to the main plasticizing blending zone through the main feed port for melt blending; the barrel heating temperature of the main plasticizing blending zone is set to 180℃-190℃; and before mixing, the polylactic acid and methyl methacrylate-butadiene-styrene copolymer are dried at 60℃-65℃ for 3.0h-4.0h.
[0045] Specifically, before melt blending, polylactic acid and methyl methacrylate-butadiene-styrene copolymer are placed in a forced-air drying oven and dried at 60℃-65℃ for 3.0h-4.0h. The dried powder and granules are fed into the main plasticizing and blending zone of a twin-screw extruder through the main feed port. The barrel heating temperature of the main plasticizing and blending zone is set to 180℃-190℃. Under the combined action of the strong shear force formed by the forward conveying element and the kneading block and the barrel heat, the polylactic acid matrix reaches a molten state. The outer shell of the methyl methacrylate-butadiene-styrene copolymer entangles and becomes compatible with the polylactic acid melt under high-temperature shear, forming a blend system in which polylactic acid is the marine phase and the copolymer is the island phase.
[0046] S2. The blended melt formed in step S1 enters the dynamic melt sealing section. The material is forcibly compressed and fills the cross-section of the barrel in the dynamic melt sealing section, forming a melt sealing zone that prevents gas-liquid backflow.
[0047] Specifically, the blended melt output from the main plasticizing blending zone is pushed into the dynamic melt sealing section by the screw. In the dynamic melt sealing section of the twin-screw extruder, the screw configuration consists of a combination of a reverse thread element and a left-handed kneading block. The ratio of the length of this section to the diameter of the twin screw, L / D, is set to 2.0-3.0. The spiral direction of the reverse element is opposite to the overall extrusion and conveying direction of the material, generating a reverse thrust on the blended melt. Under the bidirectional extrusion of forward feeding and reverse thrust, the blended melt of polylactic acid and copolymer is densified in the dynamic melt sealing section, eliminating voids between materials. This allows the high-viscosity melt to completely fill the annular gap between the barrel and the screw surface. This filled material section forms an isolation wall inside the barrel, allowing only the high-viscosity melt, which is forcibly pushed by the screw, to pass through in one direction.
[0048] S3. Pre-molten C5 petroleum resin is injected through an interface located on the side wall of the barrel in the side-injection mixing zone. The liquid C5 petroleum resin undergoes weak shear mixing with the blended melt that passes through the dynamic melt sealing section. The liquid C5 petroleum resin is injected into the side-injection mixing zone through a melt gear pump. The injection pressure of the melt gear pump is higher than the working melt pressure of the barrel in the side-injection mixing zone, and the pressure difference is controlled between 0.5 MPa and 1.2 MPa. The barrel heating temperature of the side-injection mixing zone is set at 160℃-165℃. The screw configuration in the side-injection mixing zone is a combination of a large-lead positive wide-pitch conveying element and a narrow-tooth mixing element. The C5 petroleum resin is preheated to 145℃-155℃ until completely melted before injection.
[0049] Specifically, C5 petroleum resin is pre-placed in an external melt storage tank and heated to a completely molten, low-viscosity liquid state at 145℃-155℃. A melt gear pump connected to the storage tank is then started, injecting the liquid C5 petroleum resin into the barrel through an interface on the side wall of the side-injection mixing zone barrel. During injection, the speed of the melt gear pump is adjusted to ensure that the injection pressure at the gear pump is higher than the working melt pressure of the barrel in the side-injection mixing zone, maintaining a pressure difference of 0.5MPa-1.2MPa. Under this slight positive pressure difference, the liquid C5 petroleum resin... It directly penetrates the surface of the polylactic acid melt and enters its interior; at the same time, the barrel heating temperature of the side-injected mixing zone drops to 160℃-165℃ in stages. The screw configuration in this section adopts a combination structure of a large-lead forward wide-pitch conveying element and a narrow-tooth mixing element; due to the obstruction of the dynamic melt sealing section formed in step S2, the low-viscosity liquid C5 petroleum resin injected into the barrel can only move downstream of the extruder with the main fluid. Under the reduced temperature and the weak shear field provided by the wide-pitch element, the liquid C5 petroleum resin disperses between the polylactic acid molecular chain segments for surface coating.
[0050] S4. The material mixed in step S3 enters the extrusion and shaping zone for shaping. It is then extruded through the die, cooled, and pelletized to obtain the PLA composite material. The temperature of the extrusion and shaping zone is set to 150℃-155℃, and the screw speed of the twin-screw extruder is set to 120rpm-180rpm. The extruded material is introduced into a water tank at 20℃-25℃ for traction cooling for 1.5m-2.0m, and the pellet length is cut to 2.5mm-3.0mm.
[0051] Specifically, the temperature in the extrusion setting zone is set at 150℃-155℃, and the overall screw speed of the twin-screw extruder is maintained at 120rpm-180rpm. The material is extruded into a continuous cylindrical sample through a multi-hole die, and then introduced into a cooling water tank with a water temperature of 20℃-25℃. The traction cooling length is 1.5m-2.0m. After solidification, the sample is dried by an air knife and then fed into a pelletizer to be cut into particles with a length of 2.5mm-3.0mm.
[0052] To verify the technical advantages of this invention in fermentation efficiency, tensile properties, and melt flow rate, the following embodiments and comparative examples are designed:
[0053] Example 1: By weight percentage, the composition is 83.5% polylactic acid (PLA), 15.0% methyl methacrylate-butadiene-styrene copolymer (MBS), and 1.5% C5 petroleum resin. The raw materials were dried in a forced-air drying oven at 60°C for 3 hours, and then granulated by twin-screw extrusion according to the formula (temperatures of each section are 190°C, 185°C, 185°C, 180°C, 170°C, 160°C, 160°C, 155°C, and 150°C).
[0054] Comparative Example 1: Compared with Example 1, the difference is that MBS and C5 petroleum resin were not added, the composition formulation is 100% polylactic acid (PLA), the dynamic melt sealing and side injection process is omitted, and conventional extrusion granulation is performed directly, and the rest are the same.
[0055] Comparative Example 2: Compared with Example 1, the difference is that C5 petroleum resin is missing and the amount of MBS added is different. The composition formulation is 95% polylactic acid and 5% MBS. Conventional single-pass extrusion is used, and all other aspects are the same.
[0056] Comparative Example 3: Compared with Example 1, the difference is that C5 petroleum resin is missing and the amount of MBS added is different. The composition formulation is 90% polylactic acid and 10% MBS. Conventional single-pass extrusion is used, and all other aspects are the same.
[0057] Comparative Example 4: Compared with Example 1, the difference is that: no C5 petroleum resin was added, the composition formulation is 85% polylactic acid and 15% MBS; conventional single-feed dry mixing extrusion granulation was used, and the rest were the same.
[0058] Comparative Example 5: Compared with Example 1, the difference is that the amount of C5 petroleum resin added is 5%, the composition formulation is 80% polylactic acid, 15% MBS and 5% C5 petroleum resin; and the asynchronous steps such as dynamic melt sealing and side injection in Example 1 are omitted during preparation, and conventional extrusion with one-time main feeding of ternary raw materials is adopted. All other aspects are the same.
[0059] Comparative Example 6: Compared with Example 1, the difference is that C5 petroleum resin is further in excess, and the composition formulation is 75% polylactic acid, 15% MBS and 10% C5 petroleum resin; the preparation method is conventional single-pass dry mixing extrusion with main feed, and the rest are the same.
[0060] Comparative Example 7: Compared with Example 1, the difference is that C5 petroleum resin is in extreme excess, and the composition formulation is 60% polylactic acid, 15% MBS and 25% C5 petroleum resin; conventional single-pass dry mixing extrusion with main feed is used, and all other aspects are the same.
[0061] The following test experiment will be conducted at this time:
[0062] 1. Tensile property test
[0063] Experimental preparation and equipment:
[0064] The ETM402C microcomputer-controlled electronic universal testing machine was used. The ambient temperature was set to (23±2)℃ and the relative humidity was (50±5)%. A 1A type standard dumbbell-shaped tensile specimen was selected (the gauge length of the specimen is 10.0±0.2mm wide and 4.0±0.2mm thick).
[0065] Experimental steps:
[0066] Spline dimension measurement: Using a vernier caliper with an accuracy of 0.01mm, measure the width and thickness at three different locations along the gauge length of each spline, and record the arithmetic mean as the cross-sectional area parameter of the spline;
[0067] Instrument calibration and clamping: Turn on the universal testing machine and zero the sensor; place the wide ends of the specimen symmetrically and evenly in the upper and lower wedge clamps of the testing machine, tighten the clamps, and ensure that the longitudinal axis of the specimen coincides with the center line of the clamp to avoid eccentric stress;
[0068] Parameter setting and testing: Set the tensile speed to a constant 10 mm / min in the testing machine control software; start the test program, and the testing machine will begin to axially tensile the specimen until the specimen completely breaks.
[0069] Data acquisition: The instrument automatically records the load-displacement curve during the tensile process; after the test, the system calculates the tensile strength (MPa) based on the recorded maximum load and the original cross-sectional area of the specimen, and calculates the elongation at break (%) based on the gauge length displacement when the specimen breaks. Five parallel specimens are tested in each group.
[0070] 2. Impact performance test of cantilever beam
[0071] Experimental preparation and equipment:
[0072] The PIT501J plastic pendulum impact testing machine was used. A standard specimen with a single-sided V-notch was selected, with dimensions of 80mm × 10mm × 4mm, a V-notch depth of 2.0mm, and a notch bottom curvature radius of 0.25mm. The test environment temperature was (23±2)℃.
[0073] Experimental steps:
[0074] Notch size verification: Use vernier calipers and a projector to verify the remaining width at the bottom of the notch in the spline to ensure that the dimensional accuracy meets the requirements;
[0075] Pendulum calibration: Select a pendulum with an appropriate range (e.g., 2.75J or 5.5J pendulum) based on the expected impact strength of the sample. Raise the pendulum to the predetermined height and lock it. Release the pendulum without placing the sample and perform a dry strike once, recording the pointer deflection scale to correct the pointer zero-point error caused by air resistance and bearing friction.
[0076] Spline clamping and centering: Place the spline vertically into the base vise, ensuring the notch of the spline faces away from the impact direction of the pendulum (i.e., the side of the pendulum striking surface that contacts the side without the notch). Use a centering template (centering device) to adjust the height and position of the spline, ensuring the bottom of the V-notch is flush with the vise clamping position. Tighten the vise to secure the spline.
[0077] Impact test: Press the release button, the pendulum falls freely and impacts and breaks the spline, the pointer rises with the pendulum and stops at the maximum amplitude;
[0078] Data acquisition: Read the impact absorption energy (J) indicated by the dial pointer, and use the absorption energy to divide the initial cross-sectional area at the notch of the spline to obtain the cantilever beam impact strength (kJ / m²). Five parallel splines are tested in each group.
[0079] Experiment 3: Melt Flow Rate (MFR) Test
[0080] Experimental preparation and equipment:
[0081] A standard melt flow rate tester (including a temperature-controlled barrel, piston rod, standard die, load weights, and automatic cutting device) was used. The inner diameter of the die was 2.095±0.005mm, and the length was 8.000±0.025mm.
[0082] Experimental steps:
[0083] Instrument heating and temperature control: Turn on the power to the measuring instrument and set the heating zone temperature to a constant 190℃. Start the experiment after the temperature has stabilized for at least 15 minutes.
[0084] Feeding and compaction: Weigh 4.0g of the composite material particles to be tested and quickly add them into the material cylinder through a funnel. Insert the piston rod and gently press the piston by hand to expel the air between the materials in the material cylinder, so that the material is compacted above the die.
[0085] Preheating and loading: The material is preheated and melted without load in the barrel for a time strictly controlled within 300 seconds (5 minutes). After preheating, a standard load weight with a total mass of 2.16 kg is placed stably on the top tray of the piston rod.
[0086] Extrusion and Cutting: Under the action of gravity, the melt begins to be extruded from the standard die at the bottom. When the extrudate is uniform, continuous and free of bubbles, the automatic cutting device is started, the cutting interval is set to 6 seconds, the initially extruded sample is discarded, the middle extruded sample is collected, and 5 sample segments are cut continuously.
[0087] Data Acquisition and Calculation: After the sample segments have completely cooled, the mass of each segment was weighed sequentially using an analytical balance with an accuracy of 0.0001g, and the arithmetic mean (unit: g) was taken. The melt flow rate (MFR) was calculated in g / 10min using the formula MFR = (average mass / 6s) × 600s.
[0088] Based on the above testing steps, the objective test data of Example 1 and each comparative example are compiled as follows:
[0089] Group Preparation process characteristics Tensile strength (MPa) Elongation at break (%) Impact strength (kJ / m²) Melt flow rate (MFR) (g / 10min) Example 1 Dynamic melt sealing and lateral micro-pressure injection are employed. 42.85 8.542 1.156 10.25 Comparative Example 1 conventional process 19.047 0.642 0.496 7.932 Comparative Example 2 conventional process 22.412 4.164 0.66 12.54 Comparative Example 3 conventional process 27.856 5.186 0.698 7.27 Comparative Example 4 conventional process 39.124 5.829 0.714 8.496 Comparative Example 5 conventional process 46.865 7.085 1.071 5.86 Comparative Example 6 conventional process 13.644 5.185 1.004 11.74 Comparative Example 7 conventional process 52.771 1.625 0.342 Unable to measure
[0090] Polylactic acid (PLA) matrix itself exhibits extremely high brittleness. Conventional modification involves introducing methyl methacrylate-butadiene-styrene copolymers with core-shell structures. These copolymers rely on the entanglement of the outer shell with PLA and the deformation of the inner core of butadiene to absorb impact energy. However, the traditional one-step blending process can cause damage to the microstructure when C5 petroleum resin is introduced. Under strong shear and continuous high temperature, low molecular weight C5 resin can easily penetrate the outer shell of the copolymer and invade the interior of the butadiene rubber core, causing swelling of the rubber phase and loosening of the skeleton. This collapse of the microstructure manifests as a precipitous drop in the tensile strength of the material. At the same time, the free volume of the continuous phase of the matrix is severely disturbed, leading to uncontrollable and violent fluctuations in the melt flow rate. In some cases, excessive plasticization can even cause the loss of the basis for normal rheological measurements.
[0091] This invention, by forcibly constructing a dynamic melt sealing section inside the extruder, not only independently encapsulates the strong shear compatibility process of polylactic acid and copolymer, but also avoids the reverse backflow of low-viscosity fluid at the fluid dynamics level. The pre-molten trace amount of C5 petroleum resin, relying on a micro-positive pressure difference, instantly cuts into the interior of the polylactic acid melt in the weak shear zone after cooling. Through a dual isolation mechanism in space and time, the liquid C5 can only be free between the macromolecular chain segments of the continuous phase of polylactic acid, or coat the periphery of the island phase nodes of the copolymer. It deprives the conditions for destroying the butadiene rubber core from the concentration threshold and shear dynamics, and completely fixes the core-shell structure of the toughening phase.
[0092] Supported by this specific microstructure, the various mechanical and rheological test parameters of the composite material are synergistically achieved. The absolutely intact copolymer island network can efficiently transmit external stress and induce crazes to absorb energy when subjected to force, thereby endowing the material with extremely high tensile strength and impact strength. The trace amounts of C5 resin distributed freely in the free volume of polylactic acid molecular chains play a role in inter-chain lubrication at the molecular level, weakening the frictional resistance between polymer chains, offsetting the sudden increase in matrix viscosity caused by the addition of copolymers, accurately adjusting the melt flow rate to a suitable range for smooth printing, and providing sufficient space for molecular chain slippage when the material is stretched, so that the elongation at break and melt flow properties of the material reach the optimal state simultaneously.
[0093] In summary, by strictly anchoring C5 petroleum resin within a trace range of 1.5% to 2.0%, abandoning the traditional process of direct extrusion with full-component dry mixing, and instead utilizing reverse-threaded elements and left-handed kneading blocks to reconstruct the local configuration of the twin-screw extruder, a dynamic melt sealing section is built inside the barrel. This forcibly separates the extrusion flow field into a strong shear entanglement zone at the front and a weak shear coating zone at the rear. Combined with the micro-positive pressure differential lateral injection technology in the pre-molten state, the intrusion path of low-viscosity liquid resin flowing back to the high-pressure zone is directly cut off at the hydrodynamic level. At this point, the spatial phase sequence isolation mechanism forcibly directs the microscopic penetration trajectory of the material, forcing extremely small amounts of low molecular weight resin to penetrate. The resin can only exist freely within the free volume between the macromolecular chains of the polylactic acid continuous phase. This deprives the resin of the prerequisites for breaking down the outer shell of the copolymer and destroying the inner rubber core of the butadiene from both the concentration threshold and shear force. On the basis of maintaining the force transmission of the copolymer island phase nodes and inducing the integrity of the crazing, the free low-molecular-weight resin precisely weakens the frictional resistance between the polymer chain segments of the matrix, offsetting the surge in melt viscosity caused by the introduction of the rubber phase. Relying on the fixation of this micro-phase structure, a precise parameter closed loop is completed between the tensile stiffness of the composite material, the impact fracture absorption energy, and the critical melt flow rate suitable for smooth extrusion in the FDM molding process.
[0094] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A PLA composite material based on MBS melt blending modification, characterized in that, The composite material comprises the following components by weight percentage: Polylactic acid: 83.0%-88.5%; Methyl methacrylate-butadiene-styrene copolymer: 10.0%-15.0%; C5 petroleum resin: 1.5%-2.0%; The sum of the weight percentages of the above components is 100%.
2. The PLA composite material based on MBS melt blending modification according to claim 1, characterized in that, The methyl methacrylate-butadiene-styrene copolymer is a copolymer with a core-shell structure, wherein the inner core of the core-shell structure is a butadiene rubber phase, and the outer shell is composed of styrene and methyl methacrylate.
3. The PLA composite material based on MBS melt blending modification according to claim 1, characterized in that, In the microstructure of the composite material, the methyl methacrylate-butadiene-styrene copolymer is dispersed as an island phase in the continuous phase composed of polylactic acid, and the C5 petroleum resin is distributed between the molecular chains of the continuous phase.
4. A method for preparing a PLA composite material based on MBS melt blending modification, wherein the method for preparing the PLA composite material based on MBS melt blending modification as described in any one of claims 1-3 is characterized in that, The preparation is carried out using a twin-screw extruder, which is provided with a main plasticizing and blending zone, a dynamic melt sealing section, a side-injection mixing zone, and an extrusion shaping zone in sequence along the material conveying direction. The preparation method includes the following steps: S1. The dried polylactic acid and methyl methacrylate-butadiene-styrene copolymer are added to the main plasticizing blending zone through the main feed port for melt blending; S2. The blended melt formed in step S1 enters the dynamic melt sealing section. The material is forcibly compressed and fills the cross-section of the barrel in the dynamic melt sealing section, forming a melt sealing zone that prevents gas-liquid backflow. S3. The pre-molten C5 petroleum resin is injected through an interface located on the side wall of the barrel in the lateral injection mixing zone. The liquid C5 petroleum resin is then weakly sheared mixed with the blended melt that passes through the dynamic melt sealing section. S4. The material mixed in step S3 enters the extrusion and shaping area for shaping, and is extruded through the die, cooled and pelletized to obtain the PLA composite material.
5. The method for preparing PLA composite material based on MBS melt blending modification according to claim 4, characterized in that, In the twin-screw extruder, the dynamic melt sealing section is composed of a reverse threaded element and a left-handed kneading block, and the ratio of the section length of the dynamic melt sealing section to the diameter of the twin screw, L / D, is 2.0-3.
0.
6. The method for preparing PLA composite material based on MBS melt blending modification according to claim 4, characterized in that, In step S3, the liquid C5 petroleum resin is injected into the side-injection mixing zone through a melt gear pump. The injection pressure of the melt gear pump is higher than the working melt pressure of the barrel in the side-injection mixing zone, and the pressure difference is controlled between 0.5MPa and 1.2MPa.
7. The method for preparing PLA composite material based on MBS melt blending modification according to claim 4, characterized in that, In step S1, the barrel heating temperature of the main plasticizing blending zone is set to 180℃-190℃; In step S3, the barrel heating temperature of the lateral injection mixing zone is set to 160℃-165℃.
8. The method for preparing PLA composite material based on MBS melt blending modification according to claim 4, characterized in that, In step S4, the temperature of the extrusion setting zone is set to 150℃-155℃; the screw speed of the twin-screw extruder is set to 120rpm-180rpm.
9. The method for preparing PLA composite material based on MBS melt blending modification according to claim 4, characterized in that, In step S3, the screw configuration set in the lateral injection mixing zone is a combination structure of a large lead positive wide pitch conveying element and a narrow toothed mixing element.
10. The method for preparing PLA composite material based on MBS melt blending modification according to claim 4, characterized in that, Before mixing in step S1, the polylactic acid and methyl methacrylate-butadiene-styrene copolymer are dried at 60℃-65℃ for 3.0h-4.0h. In step S3, the C5 petroleum resin is preheated to 145°C-155°C until completely melted before injection; In step S4, the extruded material is introduced into a water tank at 20℃-25℃ for traction cooling for 1.5m-2.0m, and the length of the cut particles is 2.5mm-3.0mm.